Eros and Postmodern Nihilism : A Psychoanalytical Reading of Don Delillo's Zero K 2016 - Guenou, Sarah; Nouioua, Amira Wafa (University of Ammar Theledji -Laghouat, 2022)
This dissertation examines the relationship between nihilism and postmodernism through a psychoanalytical reading of Don Delillo‘s Zero k, and is divided into three chapters. Beginning with Insights of postmodern literature, Theories about nihilism, dystopian fiction, and the relationship between them. Also, it will provide a psychoanalysis study that aims at bringing together the theories used and the historical context of the novel dealt with. In addition, it will attempt through the use of Freud‘s theory of drive life EROS that is the life instinct innate in all humans and the desire to create life and favors productivity and construction. Lyotard ,Baudrillard and Vattimo‘s theories will be mentioned as well. Moreover, it will explain the idea of the postmodernism theory through discussing a prior study made on the relationship between the nihilism and postmodernism that touches on almost all concepts of life from principles to lifestyles, from art to literature